Relationship between biometric characteristics with semen quality of buffalos (Bubalus bubalis) - Juanita Velásquez; Juan E. Duque; Juan D. Montoya; Alexandra Usuga (Revista Científica)
Several factors, including environmental and nutritional management, as well as individual-associated intrinsic factors, influence dramatically the semen quality. This study aimed to relate biometric characteristics with the semen quality of buffalos (Bubalus bubalis). For this purpose, 11 Murrah buffaloes between 2 and 7 years old, located at the Centro de Investigaciones de Biotecnología Bufalina (CIBB) in Antioquia, Colombia, were used under the same feeding and management conditions. Each buffalo underwent a complete breeding soundness examination; scrotal circumference was assessed by a scrotometer, accessory sex glands were assessed by rectal palpation and ultrasonography, and libido was assessed on a 1-10 scale by observing sexual stimulation signs. For four months, a semen sample was collected weekly from each buffalo by the artificial vaginal method; the date and time of collection and the weight of each male were recorded. For each ejaculate, volume (VOL) and concentration (CON) were evaluated, and a computerized semen analysis system assessed sperm motility and kinetics, vitality, and abnormal sperm morphology (AM) by eosin-negrosin staining and the integrity of the plasma membrane by the hypoosmotic test. Descriptive statistics and a Pearson correlation analysis were performed. Means for prostate diameter, scrotal circumference, and libido were 18.7 ± 3.7 mm, 28.8 ± 3.6 cm, and 8.6 ± 0.1, respectively. Regarding seminal quality, means for VOL of 2.3 ± 1.1 ml, CON of 1470.7 ± 33.4 x 106 cells/ml, sperm vitality of 77.9 ± 10%, AM of 20.8 ± 12.5%, total motility of 88.9 ± 6.4% and progressive motility of 73.7 ± 10.4%, were found. Positive correlations (p<0.05) between buffalo weight and sperm concentration (0.32), plasma membrane integrity (0.68), and sperm kinetics were found. Also, a positive correlation (p<0.05) was observed between scrotal circumference and sperm mass motility (0.36). On the contrary, a negative correlation (p<0.05) was found between libido and slow sperm (-0.22) and non-progressive sperm (-0.34) and between the prostate diameter and these same two parameters (-0.31 and -0.33, respectively). It is concluded that biometric parameters such as buffalo weight, scrotal circumference, libido, and prostate diameter are related to the semen quality of Murrah buffalos.